Rab22A recruits BLOC‐1 and BLOC‐2 to promote the biogenesis of recycling endosomes. (7th November 2018) - Shakya, Saurabh; Sharma, Prerna; Bhatt, Anshul Milap; Jani, Riddhi Atul; Delevoye, Cédric; Gangi Setty, Subba Rao
Abstract: Recycling endosomes (REs) are transient endosomal tubular intermediates of early/sorting endosomes (E/SEs) that function in cargo recycling to the cell surface and deliver the cell type‐specific cargo to lysosome‐related organelles such as melanosomes in melanocytes. However, the mechanism of RE biogenesis is largely unknown. In this study, by using an endosomal Rab‐specific RNAi screen, we identified Rab22A as a critical player during RE biogenesis. Rab22A‐knockdown results in reduced RE dynamics and concurrent cargo accumulation in the E/SEs or lysosomes. Rab22A forms a complex with BLOC‐1, BLOC‐2 and the kinesin‐3 family motor KIF13A on endosomes. Consistently, the RE‐dependent transport defects observed in Rab22A‐depleted cells phenocopy those in BLOC‐1‐/BLOC‐2‐deficient cells. Further, Rab22A depletion reduced the membrane association of BLOC‐1/BLOC‐2. Taken together, these findings suggest that Rab22A promotes the assembly of a BLOC‐1‐BLOC‐2‐KIF13A complex on E/SEs to generate REs that maintain cellular and organelle homeostasis. Synopsis: Recycling endosomes are transient tubular intermediates that maintain cellular/organelle homeostasis. Rab22A promotes the assembly of a BLOC‐1‐BLOC‐2‐KIF13A complex on sorting endosomes to generate the recycling tubular endosomes that are required for the biogenesis of lysosome‐related organelles. Rab22A acts as a novel regulator of recycling endosome biogenesis. Rab22A recruits BLOC‐1 and BLOC‐2 on sorting endosomes and form a complex with KIF13A. Rab22A‐BLOC‐1‐BLOC‐2‐KIF13A complex modulates recycling endosome dynamics for lysosome‐related organelle biogenesis and cellular homeostasis. Abstract : Recycling endosomes are transient tubular intermediates that maintain cellular/organelle homeostasis. Rab22A promotes the assembly of a BLOC‐1‐BLOC‐2‐KIF13A complex on sorting endosomes to generate the recycling tubular endosomes that are required for the biogenesis of lysosome‐related organelles.